The synthesis of novel 4-(3,4-dimethoxyphenyl)chromenone-crown ethers and their cation binding, as determined using fluorescence spectra - SALAN, ÜMİT (TAYLOR & FRANCIS LTD, 2009)
The complexation of naftifine (NF) and terbinafine (TB) with cyclodextrins (CDs) has been investigated by UV/visible and 1H NMR spectroscopy, ROESY techniques and also ESI-MS. Both drugs form 1:1 inclusion complexes with all the CDs tested except with -CD, as deduced from the Benesi-Hildebrand plots and confirmed by ESI-MS and NMR spectroscopy (Job plot method). The K11 values for NF decrease in the order -CDmethylated -CD2-hydroxypropyl--CD-CD. The determination of the enthalpy and entropy provides information about the main driving forces in the process. The stability constants of the complexes NF--CD, TB--CD and TB--CD determined by 1H NMR spectroscopy are in agreement with the values obtained by UV. For TB--CD, the value is higher, due to the fact that the length of the TB aliphatic chain allows a deeper inclusion of the naphthalene group inside the corresponding -CD molecule, according to the 2D ROESY experiments.
Keywords: terbinafine; naftifine; cyclodextrins; inclusion complex characterisation; CHROMENONE-CROWN-ETHERS; COUMARIN DERIVATIVES; COMPLEXATION; 4-PHENYLCOUMARINS; CONDUCTOMETRY; MACROCYCLES; MOLYBDENUM; ELEMENTS; CESIUM; SERUM